2014 IEEE 8th International Symposium on Embedded Multicore/Manycore SoCs 2014
DOI: 10.1109/mcsoc.2014.25
|View full text |Cite
|
Sign up to set email alerts
|

Cloud-Based Service for eBooks Using EPUB under the Aspect of Learning Analytics

Abstract: Building a cloud-based e-learning platform using the approach of the research field of learning analytics is the overall goal of this research study. With the strengths of a cloud service it is possible to add value to the learning process for all stakeholders. With such a solution, the process of collecting, analyzing and interpreting data becomes rather easily. This research study aims to introduce a novel platform to generate interactive e-books. In order to create digitalized forms of exercise books for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Glackin et al [18] reported that using ebook in teaching significantly affects students' learning experience and improve literacy skill. Felvégi and Matthew [19] and Ebner and Prettenthaler [20] stated that using ebook with hypermedia components can improve students' potential behavior in learning. Moreover, a study by Kör et al [21] shows that instructional materials in the form of PDF and video are used more often than animation and simulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glackin et al [18] reported that using ebook in teaching significantly affects students' learning experience and improve literacy skill. Felvégi and Matthew [19] and Ebner and Prettenthaler [20] stated that using ebook with hypermedia components can improve students' potential behavior in learning. Moreover, a study by Kör et al [21] shows that instructional materials in the form of PDF and video are used more often than animation and simulation.…”
Section: Resultsmentioning
confidence: 99%
“…Felvégi and Matthew [19] and Ebner and Prettenthaler [20] stated that using ebook with hypermedia components can improve students' potential behavior in learning. Moreover, a study by Kör et al [21] shows that instructional materials in the form of PDF and video are used more often than animation and simulation. This is due to the nature of PDF and video that are easier to be prepared than animation, simulation and interactive media.…”
Section: Resultsmentioning
confidence: 99%
“…Learning Analytics can supply powerful analytical tools for teachers and researchers who can support them in improving the effectiveness of their course management and collectively improving the quality of their students' performance as well as inform, extract and visualize real-time data about student involvement and possible student success (Macfadyen & Dawson, 2010). Learning Analytics in cloud-based services, with results can help teachers and students to learn in new ways (Ebner, Prettenthaler, & Hamada, 2014). For example, Masako Furukawa et al In the development of learning analysis platforms for OUJ online courses, for detailed analysis of learning notes (Furukawa & Yamaji, 2017), apply an app to track student's online learning activities based on LMS logs and semantic similarity between sentences in messages sent on the basis of information, indicating that a learner knows his rank in a more effective learning group (Al-Ashmoery & Messoussi, 2015).…”
Section: Introductionmentioning
confidence: 99%